Identification of Potential Salivary Biomarkers in Primary Sjögren's Disease - Huang, xuejian. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023-05.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: James Baleja.; Keyword: Pharmacology.